2012
DOI: 10.1210/en.2011-2001
|View full text |Cite
|
Sign up to set email alerts
|

Stable Inhibition of Specific Estrogen Receptor α (ERα) Phosphorylation Confers Increased Growth, Migration/Invasion, and Disruption of Estradiol Signaling in MCF-7 Breast Cancer Cells

Abstract: Elevated phosphorylation of estrogen receptor α (ERα) at serines 118 (S118) and 167 (S167) is associated with favorable outcome for tamoxifen adjuvant therapy and may serve as surrogate markers for a functional ERα signaling pathway in breast cancer. It is possible that loss of phosphorylation at S118 and/or S167 could disrupt ERα signaling, resulting in aggressive ERα-independent breast cancer cells. To this end, MCF-7 breast cancer cells were stably transfected with an ERα-specific short hairpin RNA that red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Huderson et al . reports that phosphorylation of ERα increased growth and migration/invasion in MCF‐7 breast cancer cells. Sisci et al .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Huderson et al . reports that phosphorylation of ERα increased growth and migration/invasion in MCF‐7 breast cancer cells. Sisci et al .…”
Section: Discussionmentioning
confidence: 96%
“…However, the effects of ERa on migration and invasion of MCF-7 cells appear to be contradictory. Huderson et al [28] reports that phosphorylation of ERa increased growth and migration/invasion in MCF-7 breast cancer cells. Sisci et al [29] reported that cell adhesion on fibronectin and type IV collagen induced ERa-mediated transcription and reduced cell migration in MCF-7 and MDA-MB-231 cell lines expressing ERa.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that ER is transcriptionally activated by phosphorylation, which contributes to the regulation of multiple biological processes including hormone sensitivity, nuclear localization, DNA binding, protein/chromatin interactions, protein stability, and gene transcription (32,33). The most common phosphorylation sites reported by numerous laboratories are serine 118 (Ser118) and serine 167 (Ser167; ref.…”
Section: Neddylation Pathway Inactivation Regulates Er-a Expressionmentioning
confidence: 99%
“…ERα phosphorylated at serine 118 (S118) in the Activation function-1 domain localizes preferentially at promoters of ER responsive genes ( Weitsman et al , 2006 ). This binding is critical for increased cell growth and resistance to apoptotic cell death ( Huderson et al , 2012 ), supporting the hypothesis that activation at this key phosphorylation site is a potential surrogate for a functional ERα signaling pathway in breast cancer. (4) Apoptosis evasion : Well recognized as a characteristic of cancer cells, induction of apoptotic cell death is a common objective of all forms of cancer treatment, i.e.…”
Section: Discussionmentioning
confidence: 53%